(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: to assess the level of knowledge of the nursing staff of the medical clinic of a university hospital about pressure injuries. Method: descriptive-exploratory study, approved by the Research Ethics Committee. Data were collected through a validated questionnaire. Fifty individuals participated, 35 nursing technicians and 15 nurses. Results: nursing technicians had an average of 83.5% and nurses had an average of 89.9%. A regression model was carried out to verify variables that influence the level of knowledge, and it was identified that having more than 5 years in the profession increases 1.61 times the chance that the professional has adequate knowledge. Conclusion: a weakness in knowledge about pressure injuries was identified. In view of the costs involved in the treatment and complications arising from these injuries, health institutions must implement educational actions about this condition.